2005
DOI: 10.1063/1.2031347
|View full text |Cite
|
Sign up to set email alerts
|

Stretching of material lines in shock-accelerated gaseous flows

Abstract: A Mach 1.2 planar shock wave impulsively accelerates one of five different configurations of heavy-gas ͑SF 6 ͒ cylinders surrounded by lighter gas ͑air͒, producing one or more pairs of interacting vortex columns. The interaction of the columns is investigated with planar laser-induced fluorescence in the plane normal to the axes of the cylinders. For the first time, we experimentally measure the early time stretching rate ͑in the first 220 s after shock interaction before the development of secondary instabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…For cylindrical interfaces, a nitrocellulose membrane was used by Haas & Sturtevant (1987) to confine the test gas within the cylindrical volume. Later, the jet technique, developed by Jacobs (1992), became a primary way of forming a circular gas cylinder (Jacobs 1993;Tomkins et al 2008;Zhai et al 2014b), an elliptical gas cylinder (Zou et al 2010), two gas cylinders (Tomkins et al 2003), three gas cylinders (Kumar et al 2005) and a gas curtain (Orlicz et al 2009;Balakumar et al 2012;Tomkins et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For cylindrical interfaces, a nitrocellulose membrane was used by Haas & Sturtevant (1987) to confine the test gas within the cylindrical volume. Later, the jet technique, developed by Jacobs (1992), became a primary way of forming a circular gas cylinder (Jacobs 1993;Tomkins et al 2008;Zhai et al 2014b), an elliptical gas cylinder (Zou et al 2010), two gas cylinders (Tomkins et al 2003), three gas cylinders (Kumar et al 2005) and a gas curtain (Orlicz et al 2009;Balakumar et al 2012;Tomkins et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al also observed that this density-gradient steepening will feed back into the dynamics of the flow through the baroclinic term and in fact leads to increased secondary baroclinic vorticity production, which at intermediate times becomes significant in regions of high acceleration (where ∇p becomes significant in addition to the enhanced ∇ρ). Kumar et al (2005) performed an experimental study of shock-induced mixing using PLIF visualization for several initial configurations of gaseous inhomogeneities. They examined one aspect of mixing at early time, namely the stirring of the fluid by the primary instability.…”
Section: Introductionmentioning
confidence: 99%
“…Intricate experiments with three gas cylinders have been performed (44), and others are currently under way to further stress computational fluid dynamics models.…”
Section: A Computational Fluid Dynamics Model For Shock-induced Mixinmentioning
confidence: 99%